Hermeneutics in music : Joseph Campbell and Vladimir Propp theories and their influence on the classical sonata form (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2017)
The purpose of this essay is to provide a systematic hermeneutic approach applied to tonal musical language and the morphological structures of it´s derivatives allowing to "reconnect" music with the socio-political situation of which it has always belonged, not in a receptive manner but also active, contributing to the feedback of a patriarchal ideological system existing for approximately the past four thousand years while, paradoxically offering strategies to deconstruct such ideology
Keywords: Hermeneutics; Monomyth; Sonata; Symbology; Subdominant